PENGARUH LAYANAN PENGGUNA PERPUSTAKAAN TERHADAP MOTIVASI BELAJAR MAHASISWA PPKN FKIP UNIVERSITAS RIAU ANGKATAN 2013, 2014 DAN 2015 - Gultom, Ester; Hambali, Hambali; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The library is the heart of the university. Because the library at the college has a very important position. Library services should be more attractive, friendly, fast and accurate on the needs of users or students to anticipate developments in technology and information as well as friendly services in order to motivate student learning as the dominant user. From that sense, the nature of the library is a learning resource center and information source for the wearer. Formulation of the problem in this research is: "Is there any significant effects library user services to students learning motivation PPKn FKIP University of Riau force in 2013, 2014 and 2015" ?. This study aims to determine the effect of a library user services to students learning motivation PPKn FKIP University of Riau force in 2013, 2014 and 2015. The research was conducted in PPKn FKIP Riau University Pekanbaru in April 2016. Samples were as many as 46 students with Random Sampling technique. Data collection techniques through the inquiry, observation, documentation and literature study. Engineering analysis using quantitative descriptive analysis using simple linear regression equation with the process through the application SPSS version 17.00.Based on the test results Significance performed in this study shows that enough Influence Significance between the Library User Services (X) to the Student Learning Motivation PPKn (Y) indicated by the results of F = 6.369> F table = 4.06 with sig. (0.015) <(0.05) therefore Ho rejected and Ha accepted. Meaning Effect Library User Service Learning Student Motivation PPKn FKIP Riau University Forces in 2013, 2014 and 2015 is significant. Simple linear regression equation obtained in this study, namely Y = 78.124 + 0,384X. It is the Library User Services and Student Motivation PPKn at 78.124. And any increase in the User Library Service for one unit will increase the motivation of Student Learning PPKn of 0,384X. Thus, missed hypothesis that there is sufficient Significant Influence of Service User Library Student Learning Motivation PPKn FKIP Riau University Forces in 2013, 2014 and 2015.Key Word: Library User Services, Student Motivation PPKn